Cohort studies using 3D-CT are needed to assess whether "home Gym-Bed" exercises are beneficial against sarcopenia - Josef Finsterer (PAGEPress Publications, 2024)
I was interested to read the article by Quadrelli et al. on a study on the prevention of sarcopenia using daily "Home Gym Bed" training for 30 minutes per day over 10 years in a 70-year-old man who was examined using 3D CT imaging.1 It was found that muscle mass did not change over the 10 years despite ageing.1 It was concluded that whole-body exercise in bed can help preserve muscle mass and density in older people,1 and that advanced imaging techniques can quantify the effectiveness of non-pharmacological interventions against sarcopenia.1 The study is excellent, but some points should be discussed.[...]